Leg muscle explosive power on the accuracy of shooting soccer - Hendra Mashuri; Peby Gunarto (Universitas Sriwijaya, 2023)
Leg muscle explosive power is a real form of physical condition that contributes to the accuracy of shooting at a soccer goal. The purpose of this study is to try to relate the explosive power of the leg muscles to the accuracy of shooting soccer. This study uses a quantitative approach with a type of correlation. 25 soccer players as research subjects. The research instrument used a vertical limb muscle explosive power test and a soccer shooting accuracy test. Data analysis using Pearson product-moment. The results showed that explosive power contributed significantly to the accuracy of shooting soccer. But shooting soccer also requires contributions from other factors such as basic physical conditions which are always needed in every sports skill and psychological factors.